Comparing Methods for setting saddle height in trained cyclists - Peveler, W.; Bishop, P.; Smith, J.; Whitehorn, E. (Journal of Exercise Physiology online, 2005)
Multiple methods exist for determining the optimal seat height for cycling. Prior research suggests that setting saddle height at 109% of inseam may be optimum when examining economy. A knee angle of between 25-35° has been recommended to help prevent overuse injuries. The purpose of this study was two-fold: 1) To compare the Greg LeMond method to the heel toe method and the Hamley method (109% of inseam). 2) To determine if The Hamely method, the Greg LeMond method and the heel toe method produced results that fall between the recommended angles of 25-35°. Nineteen (male (N=14) females (N=5)) cyclists were measured for inseam leg length (cm from the floor to ischium) and multiplied by 1.09 for the Hamley method and 0.883 for the LeMond method. Knee angle was measured for all three methods using a goniometer. There was no significant difference between the Hamley and the LeMond method (p=0.917). The heel toe method was significantly lower than the Hamley method (p=0.004). The heel toe method (70% accuracy) seemed to fall into the 25-35° range more often than the LeMond (65% accuracy). To ensure that the knee angle falls within a 25- 35° knee angle it is recommended to use the Holmes method.